DIGITAL TECHNOLOGIES AS A MEANS OF ADAPTIVE LEARNING FOR HIGHER EDUCATION INFORMATICS AND MATHEMATICS - Олена Косовець; Олена Соя; Ярослав Крупський; Любов Тютюн (Фізико-математична освіта)
Formulation of the problem. In the context of online / blended learning, the relevance of research on the use of digital technologies as a means of adaptive learning for higher education in computer science and mathematics is undeniable. Implementation of the principles of adaptive learning with the help of digital technologies provides significant opportunities for individualization and differentiation of the educational process by the cognitive characteristics and educational needs of each graduate.